Association of HLA alleles with autism - Sayad A (Dove Medical Press, 2018)
Arezou Sayad,1 Mohammad Taghi Akbari,2 Rezvan Noroozi,3 Mir Davood Omrani,1,4 Hidetoshi Inoko,5 Mohammad Taheri,6 Soudeh Ghafouri-Fard1 1Department of Medical Genetics, Shahid Beheshti University of Medical Sciences, Tehran, Iran; 2Department of Medical Genetics, Faculty of Medical Sciences, Tarbiat Modares University, Tehran, Iran; 3Photochemistry Research Center, Shahid Beheshti University of Medical Sciences, Tehran, Iran; 4Urogenital Stem Cell Research Center, Shahid Beheshti University of Medical Sciences, Tehran, Iran; 5Department of Molecular Life Science, Tokai University, Hiratsuka, Japan; 6Student Research Committee, Shahid Beheshti University of Medical Sciences, Tehran, Iran Background: Autism spectrum disorders (ASD) are a group of heterogeneous neurodevelopmental disorders known by impaired social interaction and activities and abnormal repetitive behavior. As a multifactorial disorder, several genetic and immunological factors have been shown to be implicated in its pathogenesis. Methods: Among them are certain human leukocyte antigen (HLA) alleles. In the current study, we genotyped HLA-A, -B & DRB alleles in 103 Iranian ASD patients and 180 age, gender, and ethnic-matched healthy controls. Results: After Boferroni correction no allele or haplotype was associated with genetic susceptibility to ASD in Iranian population. Conclusion: Future studies are needed to assess contribution of immunological factors such as HLA alleles in ASD pathogenesis. Keywords: autism, HLA typing, immune response